PERBANDINGAN KINERJA KEUANGAN BERDASARKAN KATEGORI BUKU - Irena Anindita Setiahani; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The existence of a financial intermediary institution (banking) is very important in a modern economic system. Banking as a business entity engaged in the field of finance or financial needs trust from customers to support and facilitate the activities it does. This study aims to determine the presence or absence of CAR, BOPO, LDR, ROA differences between syariah banks in the book category 1 and book 2.. Population in this research is 11 Syariah Commercial Banks in Indonesia year 2015-2017. Given the number of population is still within the range of research, the sampling is done by census method, that is, the entire population member as the research sample. The analysis technique used is independent-samples t test. The test results indicate that there is a difference of Capital Adequacy Ratio between Book 1 and Book 2 on Sharia Public Bank which go public. So it can be concluded that there is a difference between the average CAR between Book 1 and Book 2 on Sharia Public Bank which go public. There is a difference of Operational Expense to Operational Income between Book 1 and Book 2 at the Public Bank of Sharia which go public. So it can be concluded that there is an average difference between BOPO Book 1 and Book 2 on the Sharia Public Bank which go public. There is a difference of Loan to Deposits Ratio between Book 1 and Book 2 on the Sharia Public Bank which goes public. So it can be concluded that there is a difference between the average LDR between Book 1 and Book 2 on Sharia Public Bank which go public. There is no difference in Return On Assets between Book 1 and Book 2 on Sharia Public Banks that go public. So it can be concluded that there is no difference in average ROA between Book 1 and Book 2 on Sharia Public Bank which go public.Keywords: Capital Adequacy Ratio, Operational Expense to Operating Income, Loan to Deposits Ratio, and Return On AssetsREFFERENCES------------------. 2015  Laporan Keuangan Publikasi Bank 2015-2017. Jakarta:------------------. 2015. Direktori Perbankan Indonesia 2014. Jakarta: http://www.bi.go.id//Anindita, Irma. 2011. Analisis Pengaruh Tingkat Suku Bung, CAR, NPL, dan LDR terhadap Penyaluran Kredit UMKM (Studi pada Bank Umum Swasta Nasional Periode 2003-2010).Ayuningrum, Anggrainy Putri. 2011. Analisis Pengaruh CAR, NPL, BOPO, NIM, dan LDR Terhadap ROA (Studi pada Bank Umum Go Public yang Listed pada Bursa Efek Indonesia Tahun 2005-2009). Skripsi tidak diterbitkan. Semarang Fakultas Ekonomi Universitas Diponegoro.Bank Indonesia. 2004. Peraturan Bank Indonesia Nomor 6/10/PBI/2004 Tentang Sistem Penilaian Tingkat Kesehatan Bank Umum.Bank Indonesia. 2012. Peraturan Bank Indonesia (PBI) Nomor 14/26/pbi/2012 tentang KegiatanUsaha dan Jaringan Kantor Berdasarkan Modal Inti Bank. Jakarta: http//www.bi.go.id//Bratadharma, Angga. 2014. Daya Saing Bank Kategori BUKU 1 Rendah, (Online),(http://www.infobanknews.com/2014/08/daya-saing-bank-kategoribuku-i-rendah/, diakses pada 30 November 2014).http://www.http://www.bi.go.id//Huda,Nurul dan Mohamad Heykal. 2010. Lembaga Keuangan Islam Tinjauan Teoritis dan Praktis. Jakarta: Kencana Prenada Media Group Ismail. 2011. Perbankan Syariah. Jakarta: Kencana Prenada Media Group.Kasbal, Sri Wahyuni. 2012. Analisis Pengaruh Capital Adequacy Ratio (CAR),Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net InterestMargin (NIM), dan Rasio Beban Operasional Terhadap PendapatanOperasional (BOPO) Terhadap Profitabilitas pada Perusahaan Perbankan di Indonesia (Studi Kasus Bank Devisa Periode 2006-2010). Skripsi tidak diterbitkan. Makassar Fakultas Ekonomi dan Bisnis Universitas Hasanuddin.Kuncoro, Mudrajad. 2002. Manajemen Perbankan: Teori dan Aplikasi. Yogyakarta: BPFE.Rizkita, Andra. 2013. Analisis Pengaruh CAR, BOPO, NIM, NPL, dan LDR Terhadap Perubahan Laba Perbankan yang Terdaftar di BEI. JurnalDinamika Manajemen, Vol. 2 No. 7 (3): 65-80Statistik perbankan Indonesia --- http://www.ojk.go.id/id/kanal/perbankan/data-dan-statistik/statistik-perbankan-indonesiaSumitro, Warkum. 2002. Asas-asas Perbankan Islam dan Lembaga-Lembaga Terkait BMI dan Takaful) di Indonesia. Jakarta: RajaGrafindo PersadaWibowo, Edy dkk. 2005. Mengapa Memilih Bank Syariah, Cetakan Pertama, Halaman 33. Bogor: Ghalia Indonesia.Peraturan Bank Indonesia (PBI). 27 Desember, 2012. PERATURAN BANK INDONESIA NOMOR 14/26/PBI/2012 TENTANG KEGIATAN USAHA DAN JARINGAN KANTOR BERDASARKAN MODAL INTI BANK (Online). (http://www.bi.go.id/id/peraturan/perbankan/Documents/b510cf30292c45428e25e1466e81525fpbi_142612merge1.PDF diakses 19 September 2017).Erlina Dwi Syafira. 2011. Pengaruh CAR, NPL, LDR, NIM, DAN SIZE Terhadap Risiko Bisnis Bank (Studi Komparatif Bank Umum Go Publik dan Bank Umum Non Go Publik di Indonesia Tahun 2004-2008).Fahmi Noviyandi. Analisis Pengaruh Loan To Deposit Ratio Dan Makroekonomi Terhadap Profitabilitas Perbankan Umum Syariah Di Indonesia Periode 2004q1-2009q4.Takarani, Nurjanti dan Erni Ekawati. 2003. Analisis Rasio Keuangan Dalam Memprediksi Perubahan Laba Pada Perusahaan Manufaktur Di Pasar Modal Indonesia. Jurnal Ekonomi Bisnis Dan Akuntansi. Vol. 6,No 3.